Kualitas pelayanan perpustakaan di Dinas kearsipan dan perpustakaan umum kota jambi - Purnami, Ndari; Rahman, Rahman; Yantoro, Yantoro (Indonesian Educational Administration and Leadership Journal (IDEAL), 2024)
The purpose of this study was to find out the quality of library services at the Archives and Public Libraries Office of Jambi City and to find out the supporting and inhibiting factors for the quality of library services at the Jambi City Archives and Public Library Service. This study uses a qualitative descriptive method with a case study type of research. The research subjects were library staff and several library visitors at the Jambi City Archives and Public Library Service. The technique used in this research is purposive sampling. Data collection techniques in this study using the interview method. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Based on the research that has been done, it shows that the indicators in the empathy dimension need to be increased due to the unfriendliness of library staff in providing services to library visitors. Factors supporting library services, namely the existence of tools in the form of online applications that are used to facilitate officers in providing services to library visitors. Inhibiting factors for library services, namely applications that are used as a tool to help service officers cannot be used if the PLN dies and there is no prayer room for visitors or library staff to pray. Based on this research, it is suggested that librarians increase friendliness by applying smiles, greetings and greetings and providing facilities in the form of jemsets so that officers can continue to perform services when the PLN dies and immediately build a prayer room so that visitors and librarians can pray in congregation.